Effectivity and cost-effectiveness of oral nutrition supplement on malnourished children: A literature review - Helmyati, Siti; Wigati, Maria; Rachmawati, Yuliana Novita; Syarifa, Cut Alima; Rosilia, Gifani; -, Renita (Alma Ata University Press, 2024)
Background: Child undernutrition has been a global problem that could be potentially treated with the support of food for special medical purposes, including oral nutrition supplements (ONS). This literature review aims to examine the effectiveness of ONS on growth indicators, length of stay, and the occurrence of adverse events and explore the cost-effectiveness of ONS. Methods: This review summarized findings from 16 articles. The articles were experimental, with or without comparison or control group, and examine nutrition status, other outcomes directly or indirectly related to malnutrition, and cost-effectiveness. Articles were collected from electronic database including PubMed, ProQuest, and Google Scholar with additional articles from Google search engine.Results: Some articles reported that ONS administration, good ONS consumption, and higher ONS density resulted in weight and height gain, improvements in nutrition status, and shorter length of stay compared to those who don’t receive ONS, had poor ONS consumption, and had lower ONS density, although several adverse events of ONS consumption such as gastrointestinal symptoms, diarrhea, and vomiting were also recorded. Conclusion: Studies on the cost-effectiveness of ONS are limited, yet available studies suggest ONS might potentially be a cost-effective nutrition intervention in child malnutrition treatment due to its relatively low cost which potentially reduces direct medical costs.